Advance care planning discussions among residents of long term care and designated assisted living: experience from Calgary, Alberta. Issue 1 (25th November 2013) - Dyason, Claire; Simon, Jessica; Martin, Tracy Lynn Wityk
Abstract : Objectives: Patients, physicians and the healthcare system are faced with the challenge of determining, and respecting, the medical wishes of an aging population. Our study sought to describe who participates in advance care planning (ACP) and decision-making for patients in long-term care and designated assisted living. Methods: In 2008, Alberta Health Services initiated its 'Advance Care Planning: Goals of Care Designation' (Adult) policy in the Calgary zone. This policy encouraged discussions about goals of care and used a tracking form to capture these conversations. A postpolicy implementation chart review was performed at 3 time points: at baseline, at 6 months and at 18 months post implementation in long term care (LTC) and designated assisted living sites. Results: 166 charts were reviewed and 90% had a documented goals of care order. Less than half of residents (47%) were documented as participating in conversations and they were less likely to participate if they had cognitive impairment and were living in LTC. Documented family participation was more prevalent in LTC (51% vs 11%). Nurses participated in 67% of documented conversations with only 34% of discussions documenting physician involvement. Conclusions: This study identifies the lack of documented resident participation in ACP in LTC. While this finding may be explained by the high prevalence of cognitive impairment in our population, it raises questions about the optimal approach to ACP in LTC. In this setting, ACP appears to be more about relational autonomy than it is about patient autonomy.